Development of combined composition pessaries for genital herpes treatment - Litvinova, Oleksandra; Levachkova, Julia; Zaichenko, Anna; Chernykh, Vladislava; Chushenko, Valentina (ScienceRise: Pharmaceutical Science, 2017)
Recently, the problem of therapy, as well as creation of effective remedies applied for genital herpes (GH) treatment is relevant for modern gynecology and pharmacy. Aim. Development of the combined composition pessaries containing Acyclovir and Tea tree and Thyme essential oils, together with confirmation of their pharmacological activity: antiviral and antibacterial. Methods. The analysis of the assortment of drugs for GH treatment was carried out on the basis of the materials of the State Register of Medicinal Products of Ukraine and the Compendium. The pessaries disintegration and homogeneity was performed in accordance with the SPhU 2.0 requirements. Absorption spectroscopy method at wavelength (265±2) nm was used for determination of Acyclovir concentration in the solutions during release. Study of the antiviral activity of both Acyclovir, and Tea tree and Thyme essential oils, as well as the pessaries containing Acyclovir and the essential oils, was carried out on the base of the National Academy of Medical Sciences of Ukraine, in the State Institution «Institute of Epidemiology and Infectious Diseases named after L. V. Gromashevsky» (Kiev), in the laboratory of viral infections experimental chemotherapy. The analysis of the antibacterial properties of the studied samples was carried out on the base of the State Institution «Mechnikov Institute of Microbiology and Immunology». Results. In GH therapy, Acyclovir is the most prescribed and safe anti-viral drug. In result of research it was proved that the developed remedy in pessaries form containing Acyclovir, and Tea tree and Thyme essential oils inhibits type 2 herpevirus reproduction and is effective preventive drug on the experimental model of genital herpes infection in guinea pigs. Conclusion. Combined remedies containing Acyclovir and herbal substances and showing anti-viral activity are absent on Ukrainian market. Considering the fact that pessaries have a number of advantages over the other dosage forms, development of the new remedies containing Acyclovir and Tea tree and Thyme essential oils is a promising direction for modern medicine and pharmacy